Diplomasi Lingkungan River Cleanup terhadap Pemulihan Sungai Cikapundung Tahun 2024 - Zalif Nasrudin; Iis Mulyani; Lita Sari Rahayu; Muhammad Rizki Al-Fataah; Diyah Pitaloka Rizki (Journal of Legal, Political, and Humanistic Inquiry, 2026)
Pollution of the Cikapundung River, as a source of raw water and an important public space in the city of Bandung, poses ecological and social threats due to domestic waste, livestock waste, and plastic waste. This study analyzes environmental diplomacy through the contribution of River Cleanup to the restoration of the Cikapundung River within the framework of the Sustainable Development Goals (SDGs).  The research approach is qualitative, using a case study method through literature review, documentation, and secondary data analysis on water quality and river cleanup programs. The theoretical framework uses Environmental Diplomacy and Collaborative Environmental Governance theories to explain the dynamics of cross-actor collaboration between communities, government, and the private sector. The results show that transnational collaboration facilitated by River Cleanup contributes to increased public awareness, reduced waste in several segments of the river, and strengthened river-caring community networks, thereby supporting the achievement of SDG 6, SDG 11, and SDG 17 in the Cikapundung River area.